Psychological Well Being in Athletes Disabilities - Ajeng Hayyu Sujalmo; Suryanto Suryanto (Jurnal Psikologi Teori dan Terapan, 2023)
This study aims to determine the psychological well being of athletes with disabilities. Disabilities are individuals who have physical, mental, sensory and intellectual limitations. Sports media can help people with disabilities to develop and explore hidden potentials and talents, so that with sports media people with disabilities can have achievements. Individuals are said to have psychological well being if they have six dimensions, namely self-acceptance, positive relationships with others, autonomy, mastery of the environment, goals in life and personal growth. This study uses a qualitative approach using the intrinsic case study method. Data mining techniques used were documentation and semi-structured interviews and analyzed using theory driven thematic analysis. Participants were 2 disabled athletes. The results showed that all participants, numbering two people, had good psychological well-being, were able to accept their current situation, had independence, had life goals to achieve, were able to form warm relationships with others, were able to control their environment and were able to develop their talents and abilities. personal. The results of this study will be useful as a reference for coaches with disabilities and athletes with disabilities to find out how athletes who have psychological well being are described in life. ABSTRAK Penelitian ini bertujuan untuk mengetahui psychological well being pada atlet difabel. Difabel merupakan individu yang memiliki keterbatasan fisik, mental, keterbatasan sensorik dan intelektual. Media olahraga dapat membantu difabel untuk mengambangkan, dan mengeksplorasi potensi serta bakat yang terpendam, sehingga dengan media olahraga para difabel bisa memiliki prestasi. Individu dikatakan memiliki psychological well being jika memiliki enam dimensi yaitu penerimaan diri, hubungan positif dengan sesama, autonomi, penguasaan lingkungan, tujuan dalam hidup dan pertumbuhan pribadi. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi kasus intrinsik. Teknik penggalian data yang digunakan adalah dokumentasi dan wawancara semi terstruktur dan dianalisis menggunakan analisis tematik theory driven. Partisipan berjumlah 2 orang atlet difabel. Hasil penelitian menunjukan bahwa seluruh partisipan yang berjumlah dua orang memiliki kesejahteraan psikologis yang baik, dapat menerima keadaan dirinya sekarang, memiliki kemandirian, memiliki tujuan hidup yang akan dicapai, mampu membentuk hubungan yang hangat dengan orang lain, mampu mengontrol lingkungan dan mampu mengembangkan bakat serta kemampuan pribadi. Hasil penelitian ini akan bermanfaat sebagai referensi bagi pelatih difabel dan atlet difabel untuk mengetahui bagaimana gambaran atlet yang memiliki psychological well being dalam kehidupan.